2014
DOI: 10.1007/8904_2014_330
|View full text |Cite
|
Sign up to set email alerts
|

Di-sulfated Keratan Sulfate as a Novel Biomarker for Mucopolysaccharidosis II, IVA, and IVB

Abstract: Keratan sulfate (KS) is a storage material in mucopolysaccharidosis IV (MPS IV). However, no detailed analysis has been reported on subclasses of KS: monosulfated KS and di-sulfated KS. We established a novel method to distinguish and quantify mono-and di-sulfated KS using liquid chromatography-tandem mass spectrometry and measured both KS levels in various specimens.Di-sulfated KS was dominant in shark cartilage and rat serum, while mono-sulfated KS was dominant in bovine cornea and human serum. Levels of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 44 publications
3
56
1
Order By: Relevance
“…The ratio of di-sulfated KS in total KS was significantly higher in MPS newborn patients compared to general newborns (p = 0.0001) (table 1). We have previously shown a secondary elevation of total KS and increase in ratio of di-sulfated KS in blood from older patients with other MPS types, where 40% for MPS II patients and 54% of MPS IVA had significantly higher levels of ratio di-sulfated KS in total KS (Shimada et al, 2015;Tomatsu et al, 2005;Tomatsu et al, 2014). We did not see a secondary elevation of KS in the MPS II newborn samples, possibly due to low accumulation during early stages of bone development.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The ratio of di-sulfated KS in total KS was significantly higher in MPS newborn patients compared to general newborns (p = 0.0001) (table 1). We have previously shown a secondary elevation of total KS and increase in ratio of di-sulfated KS in blood from older patients with other MPS types, where 40% for MPS II patients and 54% of MPS IVA had significantly higher levels of ratio di-sulfated KS in total KS (Shimada et al, 2015;Tomatsu et al, 2005;Tomatsu et al, 2014). We did not see a secondary elevation of KS in the MPS II newborn samples, possibly due to low accumulation during early stages of bone development.…”
Section: Discussioncontrasting
confidence: 44%
“…We have previously shown that blood from patients with other forms of MPS (IV, VI, and VII) contain elevated levels of other GAGs, but we do not have access to newborn DBS from such patients at this time and cannot directly determine GAG levels expected in newborn DBS from all MPS types (Tomatsu et al, 2005;Rowan et al, 2013;Shimada et al, 2014b;Tomatsu et al, 2014;Shimada et al, 2015). Nevertheless, based on data from older patients, this newborn screen is likely to capture patients with a severe form of any MPS.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of both mono-sulfated and di-sulfated KS measured by LC-MS/MS in blood from patients with MPS IVA were elevated compared with age-matched controls [86]. The elevation of di-sulfated KS in MPS IVA patients was more significant than the elevation of mono-sulfated KS.…”
Section: Biomarkers For Mps Ivamentioning
confidence: 99%
“…After digestion, the samples are loaded into the LC-MS/MS for quantitation, and the results are compared with control samples (Figure 2). The LC-MS/MS method for analysis of disaccharides not only shows sensitivity and specificity for detecting all subtypes of MPS but also can monitor therapeutic efficacy in MPS patients and animal models [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. This method has an advantage of being both GAG-specific and quantitative.…”
Section: History Of Gag Assay By Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…The mass spectrometer was operated in the negative ion detection mode with thermal gradient focusing electrospray ionization. Specific precursor ion and product ion were used to quantify each disaccharide [32,67,68]. A m/z 354.29 precursor ion and m/z 193.1 product ion was used to detect the IS (chondrosine).…”
Section: Lc-ms/msmentioning
confidence: 99%